Studi Pemanfaatan Pembangkit Listrik Tenaga Surya di Infrastruktur Militer guna Mendukung Ketahanan Energi Nasional: Pemanfaatan Pembangkit Listrik Tenaga Surya di Infrastruktur Militer guna Mendukung Ketahanan Energi Nasional - Amalia, Zahra; Thamrin, Suyono; Yanto, Sri (UNIB Press, 2025)
Indonesia has a significant potential for renewable energy, particularly solar energy, which can be utilized to support national energy resilience, especially in military environments. This study aimed to examine how the potential of solar power plants can be optimized to support energy resilience, identify the challenges of its implementation, and evaluate its role in reducing dependence on fossil fuels. The research methodology involved a literature review from various relevant sources and data analysis to address the research questions. The findings indicate that solar power plants can improve the reliability of energy supply in military infrastructure, support independent operations, and reduce environmental impact by decreasing greenhouse gas emissions. The main challenges in implementing the solar plants include budget issues, planning, security, and technology integration. By addressing these challenges, the utilization of the solar plants in military settings can significantly contribute to national energy resilience and environmental sustainability.